APPLICATION OF DIGITAL PEER TEACHING-LEARNING MEDIA BASED ON ETHNOPEDOLOGY TOWARDS LEARNING INDEPENDENCE - Nuraini Fatmi; Henni Fitriani (SUJANA: Education and Learning Review, 2024)
This research aims to determine how Ethno pedagogy-based digital peer teaching media is applied to students' learning independence. The problem lies in the low ability of teachers to utilize digital-based technology facilities. The method used is quantitative. The research design used was a One-Group Posttest Design, an experiment with only one group without a comparison group. The experimental design used was a one-shot case study. In applying this method, the research only used one class by giving a questionnaire at the end of the activity, thus allowing an assessment of the results after the treatment was applied. The research results stated that the total average score for all aspects of student learning independence was 11.4, with a percentage of 76.67%. These results indicate that most students have good learning independence in studying physics using an ethnopedagogical approach. However, the self-evaluation aspect is an area that requires more attention because there are still students who need more confidence in assessing their learning progress.